Teaching gui-programming concepts to prospective k12 ict teachers: Mit app inventor as an alternative to text-based languages - (:unkn) unknown (International Journal of Research in Education and Science, 2017)
The purpose of this research is to investigate the short and long-term effects of using GUI-oriented visual Blocks-Based Programming languages (BBL) as a 2nd tier tool when teaching programming to prospective K12 ICT teachers. In a mixed-method approach, the effect on academic success as well as the impact on professional opinions and preferences have been gathered for drawing deeper conclusions. Conclusively, it was understood that visual BBL increased success for students who were previously having a hard time dealing with text-based programming. However, students that were already accustomed to text-based programming have shown failure adapting to the BBL. This has been interpreted as a failure of previous programming courses in terms of enabling learning transfer. Additionally, it has been understood that employing the BBL has not been entirely effective in causing prospective ICT teachers to think that programming is a subject suitable for a considerably younger target audience. © 2017, International Journal of Research in Education and Science. All rights reserved.
Keywords: GUI-programming; Programming education; Teacher education; Visual programming